A extensão popular em educação ambiental e seus processos educativos - Souza, Tiago Zanquêta de (2017)
This research has as social practice the Popular Extension in Environmental Education, developed by an extension group formed by seven people, six students of the Environmental Engineering course, University of Uberaba and the researcher, professor of the same course. The bibliographic review reveals the existence of a close relationship between critical environmental education, popular extension and popular education, since its fundamental bases are structured in the protagonism of the subjects, in the conquest of their autonomy, freedom and emancipation, besides recognizing that the process of domination, oppression and colonization of knowledge, which is triggered by social / environmental injustice. The theoretical reference of the research is linked to that of Popular Education, Popular Extension and Environmental Education, specifically Critical Environmental Education. It has as general objective to know the educational processes that propitiate the formation of environmental engineers as environmental educators, based on the social practice previously mentioned. We opted for the qualitative research modality, which is understood as an investigation that has as central concern the examination of the data in depth, taking into account the historical and / or social perspective of the moment in which the analysis is performed. We also understand that this research is descriptive, because it exposes the characteristics of a certain population or a certain phenomenon, and it is worth, as far as the means to obtain data, of field research and bibliographical research. The observations were recorded in field diaries. To analyze the data, we are using the content analysis, in which, in the pre-analysis, the analyzed documents were the field diaries, without losing sight of the problem question and the research objectives. The transformation of the data into units of registers occurred from the interpretive convergence of the paragraphs of the field diaries. Starting from the convergence between these units, the initial, intermediate and final categories were elaborated, the latter being object of analysis and final interpretation in the thesis, which is structured as follows: Initially, in the introduction, I present my life trajectory and in it I include my academic trajectory, arriving at the doctoral research, to, from the bibliographical review, present the problematic, the problem question and the objectives of this research. The research was carried out together with a group of environmental engineering students from Uberaba University, in the city of Uberaba, who are popular extension with a group of residents of Vila Esperança II and Jardim Itália, a working community. The first chapter brings the methodological approach of the research. The second chapter presents a discussion about education and culture, education as culture and education in the context of social practices, which has popular education as a way of possibilities for overcoming existing relations of oppression. The third chapter presents a historical-critical review about the context of the Brazilian university, from its origin to the present day, looking more especially for the practice of university extension. In addition, it takes popular extension as a social practice, in order that through this look, understand it as a source of production of conversational knowledge. The fourth chapter presents a discussion about the critical concept of what we mean by sustainable development, going through an analysis of the environmental dimension of education, and then discussing Brazilian environmental education, based on the study of macro trends in the country, with emphasis on macro-education Critical Environmental Education and one of its four currents, Popular Environmental Education. The fifth and final chapter presents the analyzes and results of the research, especially around the educational processes that permeated the training of extension students in the work community.